Вычислить удобным способом 53л-(23л+29л)= (11кг+49кг)-9кг= 2м+30дм+80дм+7м=...

0 голосов
36 просмотров

Вычислить удобным способом 53л-(23л+29л)= (11кг+49кг)-9кг= 2м+30дм+80дм+7м= 4см+4см+4см+4см+4см=


Математика (19 баллов)
Дано ответов: 2
0 голосов
Начинающий (371 баллов)

53л-(23л+29л)=53-23-29=1л

(11кг+49кг)-9кг=11+49-9=51кг

2м+30дм+80дм+7м=2м+7м+30дм+80дм=9м+110 дм=10м10дм

4см+4см+4см+4см+4см=4*5=20см

0 голосов
(78 баллов)

(53л-23л)- 29л=30л-29л=1л

11кг+(49-9)=11+40=51

(2м+7м)+(30дм+80дм)=9м+110дм=9м+11м=20м

4см*5=20см

...